Predictors of self-care behaviors and glycemic control among patients with type 2 diabetes mellitus - Babazadeh, Towhid; Lotfi, Yosef; Ranjbaran, Soheila (Frontiers in Public Health, 2023)
Aims: This study was conducted to use the Extended Theory of Reasoned Action (ETRA) in predicting the self-care behaviors and HbA1c among patients with type 2 diabetes in Iran. Materials & Methods: A cross-sectional study was performed using a multistage random sample. 240 patients with types 2 diabetes who were referred to the diabetes healthcare centers in Chaldoran, entered to the research. Instruments consisting standardized questionnaires were used to base on the Extended Theory of Reasoned Action (ETRA) constructs and the summary scale of diabetes self-care behaviors measure. Findings: The results of this study demonstrated that demographic variables explained approximately 7% (p-value= 0.23), and ETRA constructs 18% variance (p-value= 0.02) in the behavioral intention, respectively. The hierarchical multiple linear regressions conducted with self-care behaviors indicated demographic characteristics determined 45.7% of variance of the self-care behavior (p-value<0.001) and knowledge, attitude, self-efficacy as well as behavioral intention accounted for 63.4% of variance of the self-care behavior (p-value <0.001). Almost 57% of the variation in the HbA1c is explained by the ETRA constructs, self-care behaviors, and the demographic variables. The strongest predictor of HbA1c was the self-care behaviors (β= - 0.593). Conclusion: ETRA constructs and self-care behavior can be the best determinants of HbAc1 level among with type 2 diabetes. This model is suggested to be applied designing intervention programs to improvement HbA1c in these group of patients.